2000
DOI: 10.1149/1.1393996
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of Porous Silicon Photoluminescence by Ammonia Hydrogen Peroxide Mixture

Abstract: Low resistivity p‐type porous silicon (PS) samples are subjected to oxidation treatment in an ammonia hydrogen peroxide mixture (APM) and to etching in 0.00035% and 0.0014% ammonia solutions at room temperature for 10 to 2700 s. Photoluminescence (PL) properties of the treated PS are correlated with chemical states and microstructures analyzed by Fourier transform infrared (FTIR) spectroscopy and scanning electron microscopy (SEM). The intensity of the red PL from PS is increased by 0.00035% ammonia solution, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…Similar results have been presented in the literature with HNO 3 and SC2 oxidation. , However, Fukuda et al . have reported SC1-L to remove the surface hydrides almost completely, and Li et al have reported the SC1 solution to remove the surface hydrides completely.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Similar results have been presented in the literature with HNO 3 and SC2 oxidation. , However, Fukuda et al . have reported SC1-L to remove the surface hydrides almost completely, and Li et al have reported the SC1 solution to remove the surface hydrides completely.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results have been presented in the literature with HNO 3 and SC2 oxidation. 24,25 However, Fukuda et al 26 have reported SC1-L to remove the surface hydrides almost completely, and Li et al 25 have reported the SC1 solution to remove the surface hydrides completely. The large discrepancy is at least partially due to the fact that in studies by Li et al and Fukuda et al the PSi samples were rinsed with water after preparation.…”
Section: ■ Resultsmentioning
confidence: 99%